A cloud–based teaching framework: an introduction. (13th April 2015) - Saadatdoost, Robab; Sim, Alex Tze Hiang; Jafarkarimi, Hosein; Saadatdoost, Leila
One of the most significant discussions in education and information technology is cloud computing. Over the past six years, researchers have shown an increased interest in cloud computing for educational contexts. However, these rapid changes in information technology have a serious effect on teaching frameworks. Concerns have been raised about how cloud computing can be integrated with teaching frameworks and if it can improve teaching. In this paper, the Danielson Teaching Framework, which focuses on key aspects of teaching, was used. This framework has divided complex teaching activities into components such as communicating with students, students engagement and others which all might be improved by cloud computing; using cloud computing has capability to enhance performance of teaching. This paper seeks to address the domains of teaching frameworks and introduce an initial version of a cloud–based teaching framework that considers cloud computing can provides insight to future research on teaching frameworks.